2022
DOI: 10.3390/su14159395
|View full text |Cite
|
Sign up to set email alerts
|

Response of Phytogenic Additives on Enteric Methane Emissions and Animal Performance of Nellore Bulls Raised in Grassland

Abstract: The objective of this study was to evaluate the intake and digestibility of nutrients, emission of enteric CH4, and productive performance of Nellore bulls grazing Urochloa brizantha cv. Marandu palisade grass pastures during the rainy season, receiving an energy supplement or mineral supplement, with or without the inclusion of phytogenic additives. Forty-eight Nellore bulls were treated with: (1) energy supplement without the inclusion of phytogenic additives; (2) energy supplement with the inclusion of phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…In addition, the PHA allowed a reduction of genera Ruminiclostridium 6, Ruminococcaceae UCG-010, and Lachnospiraceae uncultured belonging to the Firmicutes phylum, Clostridiales order, and typical of cellulolytic bacteria [66]. This deleterious effect of PHA also was observed in the rumen of steers supplemented with EPHA, which had a lower relative abundance of both genera Roseburia, Family XIII UCG-002, and the Veillonellaceae family, and may be associated with the lower total digestibility of DM observed with the addition of PHA in this study and the lower fiber digestibility observed by Teobaldo et al [22] in performance trial. Witzig et al [8] also observed a reduction in the relative abundance of Ruminococcus albus by chestnut and valonea tannins.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In addition, the PHA allowed a reduction of genera Ruminiclostridium 6, Ruminococcaceae UCG-010, and Lachnospiraceae uncultured belonging to the Firmicutes phylum, Clostridiales order, and typical of cellulolytic bacteria [66]. This deleterious effect of PHA also was observed in the rumen of steers supplemented with EPHA, which had a lower relative abundance of both genera Roseburia, Family XIII UCG-002, and the Veillonellaceae family, and may be associated with the lower total digestibility of DM observed with the addition of PHA in this study and the lower fiber digestibility observed by Teobaldo et al [22] in performance trial. Witzig et al [8] also observed a reduction in the relative abundance of Ruminococcus albus by chestnut and valonea tannins.…”
Section: Discussionsupporting
confidence: 65%
“…This can be justified by the sulfur content of the corn gluten meal, due to the industrial process for obtaining that uses sulphited water in one of its stages, because many Archaea use sulfur compounds as electron donors or acceptors for energy production [68]. This also is in line with the increase in the enteric CH4 daily production reported in grazing beef cattle when supplemented with energy supplements [22]. In contrast, Methanobrevibacter abundance was reduced when 1.5 g of hydrolyzable tannins were evaluated in vitro [7], indicating that tannin extract also can affect the archaea population in the rumen.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A blend of essential oils, bioflavonoids, and tannins has been found to enhance the diet digestibility and the feed conversion rate in dairy cattle [ 21 ]. However, the combination of hydrolyzable tannins and essential oils during the supplementation of grazing beef cattle had a negative impact on forage intake and digestibility [ 22 ].…”
Section: Introductionmentioning
confidence: 99%